Is there any Significant Effect of Business Process Re-Engineering Strategy on Service Delivery in the Contextualization of Food Manufacturing Companies in Kenya? - Ongeri, Richard Nyaanga; Magutu, Peterson Obara; Litondo, Kate (Archives of Business Research, 2020)
The main objective of the study was to determine if there any significant effect of business process re-engineering strategy on service delivery in the contextualization of food manufacturing companies in Kenya. Accordingly, the study sought to determine the effect of business process re-engineering strategy on service delivery of companies manufacturing food in Kenya. The population of the study comprised of the company’s manufacturing food in Kenya. A descriptive cross-sectional survey design was adopted in data collection and analysis. Primary data was collected from respondents using a structured questionnaire, while secondary data was collected from published firm’s reports. Out of the 75 respondents targeted by the study, 44 respondents forming 56.67% response rate, which was considered adequate for analysis with good representation from all the subsectors. On hypotheses testing, it was established that, 58.1% of variations in the service delivery are explained by variations in the BPR strategy namely resources mobilization for BPR, sponsorship and commitment, BPR cross-functional teams, analytical processes selection, BPR prototypes, management of re-engineered processes, clear BPR definition and vision. Thus, there is a significant relationship between BPR strategy and service delivery of companies manufacturing food in Kenya. HA1 is therefore supported. In conclusion, the study confirmed that there is a positive and statistically significant relationship between BPR strategy and service delivery of companies manufacturing food in Kenya, where 58.1% of variations in the service delivery is explained by variations in the BPR strategy namely resources mobilization for BPR, sponsorship and commitment, BPR cross functional teams, analytical processes selection, BPR prototypes, management of re-engineered processes, clear BPR definition and vision. The results therefore support the anchoring theory of resource advantage theory. This study has contributed in different areas including implications to theory, policy, management practice and methodological contributions as discussed in the subsequent paragraphs. First, this study has advanced frontiers of knowledge from the study findings; this study confirms that today’s competitive environment compels organizations to re-engineer their business processes to effect perfect service delivering for customer satisfaction which eventually leads to improved overall FP (Hussein, Bazzi, Dayekh & Hassan, 2013; Jurisch, Ikas, Wolfgang, Wolf & Kurcmar, 2012). The research findings have addressed the key gaps in this study. Secondly, this study has contributed to theory: the empirical relationship between BPR strategy and service is significant where BPR strategy constructs independently and positively influences improvements in service delivery with four significant predictors: resources mobilization for BPR; BPR cross-functional teams; sponsorship and commitment of top management; and the management of re-engineered processes. This study confirms and supports the use of resource based view theory. Thirdly on the study’s policy contributions: the study will guide policy makers to develop BPR strategies that will lead to improved service with the understanding that improved business processes facilitates organizations to maximize the value addition which eventually leads to improved service delivery. Lastly on the methodological contributions: key methodological contribution is the use of a quantitative composite index in computing the SD index, the use an integrated empirical model to test the relation between BPR strategies and service delivery; the study used a number of indicators to measure each construct, which improved the construct validity.